Trimeric structure of the mouse Kupffer cell C‐type lectin receptor Clec4f. Issue 1 (9th August 2019) - Ouyang, Zhenlin; Felix, Jan; Zhou, Jinhong; Pei, Yingmei; Ma, Bohan; Hwang, Peter M.; Lemieux, M. Joanne; Gutsche, Irina; Zheng, Fang; Wen, Yurong
Abstract : The C‐type lectin receptor Clec4f has been identified as a specific surface marker for Kupffer cells, although its ortholog is absent in humans and its biological function remains elusive. Here, we report the crystal structure of a truncated mouse trimeric Clec4f. The orientation between the carbohydrate‐recognition domain of Clec4f and its neck region differs from other C‐type lectins, resulting in an observed distance of 45 Å between the glycan‐binding sites within the Clec4f trimer. Interestingly, the trimeric coiled‐coil interface within its heptad neck region contains multiple polyglutamine interactions instead of the predominantly hydrophobic leucine zipper found in other C‐type lectin receptors. The Clec4f trimeric structure displays unique features regarding its assembly and ligand recognition, shedding light on the evolution and diversity of the C‐type lectin family. Abstract :